2020
DOI: 10.1038/s41419-019-2212-y
|View full text |Cite
|
Sign up to set email alerts
|

Piperlongumine regulates epigenetic modulation and alleviates psoriasis-like skin inflammation via inhibition of hyperproliferation and inflammation

Abstract: Psoriasis is an autoimmune skin disease, where chronic immune responses due to exaggerated cytokine signaling, abnormal differentiation, and evasion of keratinocytes apoptosis plays a crucial role in mediating abnormal keratinocytes hyperproliferation. From the therapeutic perspective, the molecules with strong anti-proliferative and anti-inflammatory properties could have tremendous relevance. In this study, we demonstrated that piperlongumine (PPL) treatment effectively abrogated the hyperproliferation and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(54 citation statements)
references
References 67 publications
2
52
0
Order By: Relevance
“…Ki67 and PCNA are classical markers of cell proliferation in a variety of diseases ( Alhosaini et al, 2021 ; Cai et al, 2021 ). As expected, following TDG treatment, the number of Ki67 and PCNA-positive cells in IMQ-induced psoriasis-like mice decreased significantly ( Figure 2 ; Supplementary Figure S1 ), which is consistent with the results of previous studies ( Ru et al, 2020 ; Thatikonda et al, 2020 ; Tomalin et al, 2020 ). Accordingly, we speculated that TDGs could mitigate the excessive proliferation of KCs to effectively alleviate psoriasis.…”
Section: Discussionsupporting
confidence: 92%
“…Ki67 and PCNA are classical markers of cell proliferation in a variety of diseases ( Alhosaini et al, 2021 ; Cai et al, 2021 ). As expected, following TDG treatment, the number of Ki67 and PCNA-positive cells in IMQ-induced psoriasis-like mice decreased significantly ( Figure 2 ; Supplementary Figure S1 ), which is consistent with the results of previous studies ( Ru et al, 2020 ; Thatikonda et al, 2020 ; Tomalin et al, 2020 ). Accordingly, we speculated that TDGs could mitigate the excessive proliferation of KCs to effectively alleviate psoriasis.…”
Section: Discussionsupporting
confidence: 92%
“…The PI3K/AKT signaling is activated in psoriatic keratinocytes and reflect cell growth promotion, induction of hyperproliferation and hyper-keratinization ( Engelman et al, 2006 ; Li et al, 2019 ; Thatikonda et al, 2020 ). Data from the gene expression analysis indicated that both LV extract and pure RA downregulated AKT .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, endotoxemia can also induce apoptosis through oxidative stress. For example, piperlongumine exhibits prominent anti-inflammatory effects by inhibiting the ETX-induced p65 NF-κB signaling cascade and markedly suppresses cytokine storm production, which is closely associated with ROS-mediated induction of late apoptosis and reduced expression of antiapoptotic Bcl2 protein (Thatikonda et al, 2020). To sum up, Figure 4 reveals how the recognition signals of endotoxin, inflammation, and oxidative stress responses induce apoptosis directly or indirectly.…”
Section: Other Anti-apoptosis Ingredients Derived From Herbal Medicinesmentioning
confidence: 99%